Gene Therapy and its Application in Dentistry - Anshul Khandelwal; Sarbani Deb Sikdar; Raj Kumar Diwan; Savita Ghom; Anil Ghom (Wolters Kluwer Medknow Publications, 2010)
As evolution is a continous process with the advancement of the technology, the researches are in continuous to understand the cellular and molecular basic of every disease. As in most of the diseases conventional method is not giving satisfactory results, thus focus is on gene therapy located to treat not only inherited disease but also acquired ones. The gene therapy has broad spectrum application in the field of dentistry like in cancerous and precancerous condition, salivary gland disorders, autoimmune diseases, bone repair, DNA vaccination, etc. Thus, aim of this article is to focus in brief of the basic of gene therapy and about its applications in the field of dentistry.